Freedom walkers : the story of the Montgomery bus boycott - Freedman, Russell (New York : Holiday House, 2006)
Presents the story of the Montgomery bus boycott in 1955 and the major persons and events that contributed to the year-long struggle for equal rights on Montgomery's city buses.
Includes bibliographical references (p. 100-110) and index.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
7.7
3-6
Keywords: African Americans -- Civil rights -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; African Americans -- Alabama -- Montgomery -- Biography -- Juvenile literature; Civil rights workers -- Alabama -- Montgomery -- Biography -- Juvenile literature; Segregation in transportation -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; African Americans -- Biography; African Americans -- Civil rights -- History; Civil rights workers; Segregation in transportation -- History; African Americans -- Biography; African Americans -- Civil rights -- History; Civil rights workers -- Biography; Segregation -- History; Montgomery (Ala.) -- Biography -- Juvenile literature; Montgomery (Ala.) -- Race relations -- Juvenile literature; Montgomery (Ala.) -- Race relations; Montgomery (Ala.) -- Race relations